2012
DOI: 10.1002/adfm.201202724
|View full text |Cite
|
Sign up to set email alerts
|

All‐Polymer Bistable Resistive Memory Device Based on Nanoscale Phase‐Separated PCBM‐Ferroelectric Blends

Abstract: All polymer nonvolatile bistable memory devices are fabricated from blends of ferroelectric poly(vinylidenefluoride–trifluoroethylene (P(VDF‐TrFE)) and n‐type semiconducting [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM). The nanoscale phase separated films consist of PCBM domains that extend from bottom to top electrode, surrounded by a ferroelectric P(VDF‐TrFE) matrix. Highly conducting poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) polymer electrodes are used to engineer band offsets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 19 publications
3
37
0
Order By: Relevance
“…High surface roughness leads to non-uniform electrical fi eld across the active layer and possibly poor yield and reproducibility for ferroelectric capacitors and low mobility and low ON/OFF ratios in ferroelectric transistors. [ 2,19,20 ] The measured surface roughness from the topography images (see the Supporting Information) of these blend fi lms annealed at 135 °C for 4 h, show relatively smooth fi lms with an increase in roughness from ∼ 2 nm for pure P(VDF-TrFE) fi lms to ∼ 5 nm for a blend fi lm with 8 wt% PPO. As seen from Figure 2 d, with increasing amounts of PPO the peak height of the amorphous PPO nanospheres increases hence leading to increase in roughness.…”
Section: Morphologymentioning
confidence: 97%
“…High surface roughness leads to non-uniform electrical fi eld across the active layer and possibly poor yield and reproducibility for ferroelectric capacitors and low mobility and low ON/OFF ratios in ferroelectric transistors. [ 2,19,20 ] The measured surface roughness from the topography images (see the Supporting Information) of these blend fi lms annealed at 135 °C for 4 h, show relatively smooth fi lms with an increase in roughness from ∼ 2 nm for pure P(VDF-TrFE) fi lms to ∼ 5 nm for a blend fi lm with 8 wt% PPO. As seen from Figure 2 d, with increasing amounts of PPO the peak height of the amorphous PPO nanospheres increases hence leading to increase in roughness.…”
Section: Morphologymentioning
confidence: 97%
“…Memory diodes have been reported that were based on phase separated blends of P(VDF-TrFE) and organic semiconducting polymers. [23][24][25][26] The structure of these blends consists of semiconducting columns in a ferroelectric matrix. The bi-stable polarization state of the ferroelectric yields the binary information that can non-destructively be read out by current through the semiconducting columns.…”
Section: Introductionmentioning
confidence: 99%
“…A similar morphology was observed when P(VDF-TrFE) was mixed with other polymeric semiconductors such as poly(9,9'-dioctyl fluorene) (PFO) [ 10 ] and poly[(9,9-di-n-octylfluorenyl-2,7-diyl)-alt- [11] as well as molecular semiconductors such as [6,6]-phenyl-C61-butyric acid methyl ester (PCBM). [12] It has been shown that liquid phase de-mixing of the blend components occurs via surface-directed spinodal decomposition during solution casting. [13] Surface tension differences determine to what extent one of the phases is preferred at an interface, and thus whether surface-directed stratification plays a (dominant) role in establishing the final phase geometry.…”
Section: Introductionmentioning
confidence: 99%